Social and Economic Impact of Industrialization Nickel Mining on The Community (Study of Wonuamorome Village, Konawe Regency) - Adriyanto Syahputra (Papsel Journal of Humanities and Policy, 2024)
The aims of this research are: 1) To determine the social impact of nickel mining on the community in Wonuamorome Village, Puriala District, Konawe Regency. 2) To determine the economic impact of nickel mining on the community in Wonuamorome Village, Puriala District, Konawe Region? The technique used in selecting informants in this research was purposive sampling. The informants selected were key informants, namely the village head and a community figure, as well as additional informants consisting of two company officials, four employees who lived in Wonua Morome Village, and four community members. So the total informants in this investigation were 12 people, and several key informants came from village officials. The emergence of industrial areas in an area is believed to bring positive and negative factors to the lives of people in that area, such as positive social impacts, namely that industry can provide employment opportunities for local residents. The presence of the business world in Wonua Morome Village opens up employment opportunities for the local community. And the negative social aspect is contact with crocodiles which can cause social conflict. The presence of the business world in Wonua Morome Village has led to land conflicts between immigrants and local residents. The positive economic impact is to increase village cash income. The presence of businesses in Wonua Morome Village increases the village's cash income. Negative economic impacts include industrial waste which is dangerous for the environment and pollutes people's agricultural land, causing losses.